2017
DOI: 10.1039/c7cp01524k
|View full text |Cite
|
Sign up to set email alerts
|

Computing distance distributions from dipolar evolution data with overtones: RIDME spectroscopy with Gd(iii)-based spin labels

Abstract: Extraction of distance distributions between high-spin paramagnetic centers from relaxation induced dipolar modulation enhancement (RIDME) data is affected by the presence of overtones of dipolar frequencies. As previously proposed, we account for these overtones by using a modified kernel function in Tikhonov regularization analysis. This paper analyzes the performance of such an approach on a series of model compounds with the Gd(iii)-PyMTA complex serving as paramagnetic high-spin label. We describe the cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 57 publications
2
70
1
Order By: Relevance
“…For such spin pairs, the RIDME time trace is acquired on the slow relaxing spin label, whereas the fast relaxing metal centeri sf lippedb ys pontaneous relaxation. [25,53] The aim of the work presented here is to establish the PDSbased approach for distance measurements between ah ighspin Fe 3 + ion and an itroxide. Recent RIDME studies on metal ion/spin label andm etal ion/metal ion pairs, such as low-spinF e 3 + /nitroxide, [6,30] low-spinF e 3 + /trityl, [51] Cu 2 + /nitroxide, [20] Mn 2 + /nitroxide, [25] and Gd 3 + /Gd 3 + , [49,[52][53][54] confirmed these advantages and showedb etter signal-to-noise ratios and less orientation selectivity as compared to PELDOR.…”
Section: Introductionmentioning
confidence: 99%
“…For such spin pairs, the RIDME time trace is acquired on the slow relaxing spin label, whereas the fast relaxing metal centeri sf lippedb ys pontaneous relaxation. [25,53] The aim of the work presented here is to establish the PDSbased approach for distance measurements between ah ighspin Fe 3 + ion and an itroxide. Recent RIDME studies on metal ion/spin label andm etal ion/metal ion pairs, such as low-spinF e 3 + /nitroxide, [6,30] low-spinF e 3 + /trityl, [51] Cu 2 + /nitroxide, [20] Mn 2 + /nitroxide, [25] and Gd 3 + /Gd 3 + , [49,[52][53][54] confirmed these advantages and showedb etter signal-to-noise ratios and less orientation selectivity as compared to PELDOR.…”
Section: Introductionmentioning
confidence: 99%
“…This allows more than two well-resolved periods of the dipolar modulation to be observed, as seen in Figure 3 violet trace. [46] Distance analysis, together with the validation procedure, was performed for all data sets recorded on the ZnG19 protein using DeerAnalysis [45] or OvertoneAnalysis [46] in the case of the LiRIDME datasets, and the same most-probable distance (2.4 nm) and similar distance distributions were obtained in all cases. Each of the two methods has its own specific factors influencing the value of the modulation depth as previously discussed: it depends on the excitation efficiency of the pump pulse for LiDEER and on the laser excitation and quantum yield for (Re)LaserIMD.…”
mentioning
confidence: 99%
“…Since the theoretical prediction of overtone coefficients appears to be difficult, Keller et al . determined them experimentally on a series of Gd 3+ ‐rulers with known Gd 3+ ‐Gd 3+ distance distributions . This calibration revealed that the overtone coefficients are independent from the mixing time and only weakly dependent on temperature and the spin‐spin distance within the range 3–6 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, as compared to Gd 3+ /Gd 3+ PELDOR, Gd 3+ /Gd 3+ RIDME might be less reliable for the measurement of long distances. The most significant challenge of Gd 3+ /Gd 3+ RIDME are the higher harmonics of the dipolar coupling frequency, namely 2 ν dd and 3 ν dd (Figure ) . These harmonics appear due to multiple quantum relaxation pathways and, together with the usual dipolar coupling frequency ν dd , modulate the RIDME time traces.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation